Personal Reflection: Teaching in the Shadow of a Dead God - Paul Corrigan (International Journal for the Scholarship of Teaching and Learning, 2013)
Excerpt: Potter (2013) argues that even though many college teachers have adopted constructivist practices and perspectives, the “foundations” of Western higher education remain objectivist through and through. In the title metaphor of his essay, “objectivism” is the dead god. Constructivism killed it conceptually. But materially and ideologically speaking, its shadow still hangs over everything we do. While we work to deeply engage learners in their own learning, the structures and infrastructures of our institutions assume a superficial understanding of learning and thereby undermine our efforts.